?CHEMICAL AND OXIDATIVE CHANGES IN FRIED BITTER GOURD AND ONION DURING STORAGE (Biological Sciences - PJSIR, 2000)
The present study was carried out to extend the shelflife ofthe fried bitter gourds and onions by the addition of antioxidant in soyabean oil during frying proc.ess. Chemical and oxidative changes in fried bitter gourds and onions were also inves- tigated during storage. Crude protein and mineral contents of both the fried vegetables remained unchanged. However, reduction in moisture contents along with marked increase in fat contents was observed in fried vegetables. Significant improvement in protein digestibility was also observed in both the vegetables after frying. Addition of antioxidant in the frying oil remarkablly reduced FFA and pay of processed vegetables during storage at 25° and 45°C. Addition of 2% antioxidant reduced FFA from 0.346 to 0.079% and pay from 91.6 to 30.0 meq kg"at 45°C on storage of fried bitter gourds while in case of onions, FFA from 0.372 to 0.055% and pay from 121.6 to 0.102 meqlKg during storage for six months. Subjective evaluation studies showed that these processed vegetables, on six months storage at 45°C, were organoleptically acceptable. Therefore, it is concluded that addition of2% antioxidant extended the shelf life of the fried vegetables up to six months.